Autologous Right Pulmonary Artery Tissue for Repair of Left Pulmonary Artery Originating from Left Patent Ductus Arteriosus in a Patient With Tetralogy of Fallot and Absent Pulmonary Valve - AKALIN, FİGEN; AK, KORAY; ARSAN, SİNAN (SPRINGER, 2011)
Left pulmonary artery (PA) originating from patent ductus arteriosus is an exceptionally rare variant of tetralogy of Fallot with absent pulmonary valve. We described an alternative technique for the repair of discontinuous left PA with the use of the redundant pulmonary artery tissue as material for the conduit in a 3-year-old boy.
Keywords: Tetralogy of fallot; Absent pulmonary valve; Autologous conduit; Patent ductus arteriosus